Balancing roles and blurring boundaries: Community health workers' experiences of navigating the crossroads between personal and professional life in rural South Africa. (4th September 2020) - Laurenzi, Christina A.; Skeen, Sarah; Rabie, Stephan; Coetzee, Bronwynè J.; Notholi, Vuyolwethu; Bishop, Julia; Chademana, Emma; Tomlinson, Mark
Abstract: As demand for health services grows, task‐shifting to lay health workers has become an attractive solution to address shortages in human resources. Community health workers (CHWs), particularly in low‐resource settings, play critical roles in promoting equitable healthcare among underserved populations. However, CHWs often shoulder additional burdens as members of the same communities in which they work. We examined the experiences of a group of CHWs called Mentor Mothers (MMs) working in a maternal and child health programme, navigating the crossroads between personal and professional life in the rural Eastern Cape, South Africa. Semi‐structured qualitative interviews ( n  = 10) were conducted by an experienced isiXhosa research assistant, asking MMs questions about their experiences working in their own communities, and documenting benefits and challenges. Interviews were transcribed and translated into English and thematically coded. Emergent themes include balancing roles (positive, affirming aspects of the role) and blurring boundaries (challenges navigating between professional and personal obligations). While many MMs described empowering clients to seek care and drawing strength from being seen as a respected health worker, others spoke about difficulties in adequately addressing clients' needs, and additional burdens they adopted in their personal lives related to the role. We discuss the implications of these findings, on an immediate level (equipping CHWs with self‐care and boundary‐setting skills), and an intermediate level (introducing opportunities for structured debriefings and emphasising supportive supervision). We also argue that, at a conceptual level, CHW programmes should provide avenues for professionalisation and invest more up‐front in their workforce selection, training and support.